Usefulness of the theory of the organizational cycle in managerial and professional work - Gawrych, Roman (PRAWO i WIĘŹ, 2024)
The content of this article shows in a synthetic way the usefulness of the theory of the organized action cycle, the concept of which was developed by a French chemist and physicist,and at the same time the organizer of work processes in various units, Henry Louis Le Chatelier.The theory was presented as a useful philosophy of efficient operationin various areas of managerial work and social life.It was pointed out that it consists of three phases: the preparation phase (defining the objectives of the action, planning, acquiring resources) as well as the implementation andcontrol phases.The article characterizes the particular phases, showing a number of their important details, such as: types of goals, features of a good plan, the process of resource management, features of an ideal efficient organization, and types of control and its validity in management.The whole work ends with a summary, which shows that the proper use of the assumptions of the organized action cycle theory can be a source of various successes in managerial work and social activity.